2023
DOI: 10.1002/tpg2.20292
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of monosaccharides contents in rice whole grain using genome‐wide association study

Abstract: The simplest form of carbohydrates are monosaccharides which are the building blocks for the synthesis of polymers or complex carbohydrates. Monosaccharide contents of 197 rice accessions were quantified by HPAEC‐PAD in rice (Oryza sativa L.) whole grain (RWG). A genome‐wide association study (GWAS) was carried out using 33,812 single nucleotide polymorphisms (SNPs) to identify corresponding genomic regions influencing neutral monosaccharides contents. In total, 49 GWAS signals contained in 17 genomic regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 146 publications
0
5
0
Order By: Relevance
“…A glycosyl hydrolase family 16 xyloglucan endotrans-glycosylase was found to be linked to the marker S8.1_12523990 associated to NHL. Recent studies have shown that xyloglucan endotrans-glycosylase, a prominent cell wall modifying enzyme, causes cell expansion, with loosening/reinforcing cell walls, particularly in response to environmental stress ( Panahabadi et al., 2022 ). They demonstrated that glycosyl hydrolase family 16 xyloglucan endotrans-glycosylase was included in brassinolide hormone biosynthesis and pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A glycosyl hydrolase family 16 xyloglucan endotrans-glycosylase was found to be linked to the marker S8.1_12523990 associated to NHL. Recent studies have shown that xyloglucan endotrans-glycosylase, a prominent cell wall modifying enzyme, causes cell expansion, with loosening/reinforcing cell walls, particularly in response to environmental stress ( Panahabadi et al., 2022 ). They demonstrated that glycosyl hydrolase family 16 xyloglucan endotrans-glycosylase was included in brassinolide hormone biosynthesis and pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this hydrolysis condition was optimal for the determination of monosaccharides in ITF. In addition, these results indicated that Fru can achieve a relatively ideal range of the hydrolysis recovery rates under mild hydrolysis conditions [30]. Once the hydrolysis conditions meet the requirements for monosaccharide release, the variation in the recovery rate is no longer dependent on whether the hydrolysis intensity is sufficient to support monosaccharide release but rather on the stability of the monosaccharide in the hydrolytic environment [27,31].…”
Section: Optimization Of Acid Hydrolysis Conditions Of Itfmentioning
confidence: 92%
“…SlIDD16 showed reduced expression in RIN mutants, suggesting its potential role in fruit ripening 93,94 . The rice orthologs SlIDD16, OsIDD11 are involved in drought tolerance by regulating stomatal movement and starch composition in rice 65,95 . OsIDD2 regulates the secondary cell wall (SCW) formation by directly binding to SCW biosynthesis genes 48 .…”
Section: Functional Analysis Of Sliddsmentioning
confidence: 99%